Emerging drugs for the treatment of non-alcoholic steatohepatitis: a focused review of farnesoid X receptor agonists. (2nd July 2020) - Shah, Raj A.; Alkhouri, Naim; Kowdley, Kris V
ABSTRACT: Introduction: The discovery of the farnesoid X receptor and its role in bile and lipid homeostasis has led to the investigation of FXR agonists as a therapy in cholestatic disorders and in NAFLD. With increasing prevalence of obesity and metabolic syndrome, NAFLD has grown to become the most prevalent chronic liver disease, present in a quarter of the worldwide population. FXR agonists represent a promising avenue for this burgeoning disease with few options for pharmacologic therapy. Areas covered: A brief overview of the epidemiology of NAFLD/NASH and a review of current evidence on available treatments is provided. For FXR agonists, a review is performed of mechanisms of action, efficacy, and adverse effects. Finally, hurdles to widespread adoption of this drug class in treatment of NASH are described. Prospective clinical trials were reviewed on the US National Library of Medicine database at clinicaltrials.gov, along with a literature search of meta-analyses, reviews, and original research. Expert opinion: FXR agonists show promise for treating NASH with positive effects on several surrogate markers of disease including liver fibrosis on biopsy, fat reduction on MRI, and decrease in liver enzymes. However, their long-term tolerability, safety, and efficacy on liver-related outcomes need to be established.